2004
DOI: 10.1016/j.jasms.2003.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Selective molecular recognition of arginine by anionic salt bridge formation with bis-phosphate crown ethers: implications for gas phase peptide acidity from adduct dissociation

Abstract: Arginine forms a stable noncovalent anionic salt bridge complex with DP (a crown ether which contains two endocyclic dialkylhydrogenphosphate esters). Abundant adduct formation with DP is observed for complexes with arginine, YAKR, HPPGFSPFR, AAKRKAA, RR, RPPGF-SPFR, RYLGYL, RGDS, and YGGFMRGL in electrospray ionization mass spectrometry (ESI-MS) experiments. DFT calculations predict a hydrogen bonded salt bridge structure with a protonated guanidinium flanked by two deprotonated phosphates to be the lowest en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…18-22,32 Addition of 18-crown-6-ether to solutions containing peptides and proteins results in preferential adduction to lysine although some binding to histidine, arginine, and the N-terminus also occurs. 20-22 Information about the number of lysine residues can be obtained for small peptides, but not all lysine residues are adducted with larger proteins, a result that has been attributed to solvent inaccessible residues.…”
Section: Introductionmentioning
confidence: 99%
“…18-22,32 Addition of 18-crown-6-ether to solutions containing peptides and proteins results in preferential adduction to lysine although some binding to histidine, arginine, and the N-terminus also occurs. 20-22 Information about the number of lysine residues can be obtained for small peptides, but not all lysine residues are adducted with larger proteins, a result that has been attributed to solvent inaccessible residues.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their high affinities for alkali ions, crown ethers also could form stable complexes with protonated amines through hydrogen bonds, a property that has been adapted for various applications of crown ethers. Beauchamp et al, Julian et al, and others developed the SNAPP (selective non-covalent adduct protein probing) technique using crown ether to probe protein sequences, which is based on the selectivity of crown ethers towards basic amino acids such as lysine, arginine, and histidine [4] . Using theoretical electronic structure calculations, Chen et al recently demonstrated that crown ethers could form non-covalent complexes with lysine, arginine and histidine [5] .…”
mentioning
confidence: 99%
“…The stronger stabilization of the MMFF structures does not only result from the differences in the bonding network between the guanidinium and carboxylate moieties, but also (8) 1.67 O(1)···HN (7), O(3)···HN (5) 2.12 N(10)···HN (9), N(11)···HN (12) 1.92 C(13)···C (14), C(15)···C (16) 3.22 MMFF2 O(1)···HN (5) 1.77 O(2)···HN (6) 1.68 O(1)···HN (7) 2.10 N(10)···HN (9) 1.91 C(13)···C (14) 3.26 O(3)···HN (7) 1.86 O(4)···HN (8) 1.63 O(3)···HN (5) 1.97 N(11)···HN (12) 1.86 C(15)···C (16) 3.57 MMFF4 O(1)···HN (5), O(3)···HN (7) 1.82 O(2)···HN(6), O(4)···HN (8) 1.66 O(1)···HN (7), O(3)···HN (5) 1.98 N(10)···HN (9), N(11)···HN (12) 1.86 C(13)···C (14), C(15)···C (16) 3.56 OPLS-AA1 O(1)···HN (5), O(3)···HN (7) 1.71 O(2)···HN(6), O(4)···HN (8) 1.67 O(1)···HN (7), O(3)···HN (5) 1.80 DZ1 O(1)···HN (5), O(3)···HN (7) 1.69 O(2)···HN(6), O(4)···HN (8) 1.71 O(1)···HN (7), O(3)···HN (5) 1.77 Figure 5. RI-MP2/TZVP optimised structures of zwitterionic arginine dimers.…”
Section: Arginine Dimersmentioning
confidence: 99%